Clinical impact of non-alcoholic fatty liver disease on the occurrence of colorectal neoplasm: Propensity score matching analysis - Yang, Young Joo; Bang, Chang Seok; Shin, Suk Pyo; Baik, Gwang Ho (PloS one, 2017)
The effect of non-alcoholic fatty liver disease (NAFLD) on the occurrences of colorectal neoplasm (CRN) at surveillance colonoscopy is rarely evaluated. We retrospectively reviewed medical records of 1,023 patients who had both index and surveillance colonoscopy at a single institution. The cumulative occurrence rates of overall and advanced CRN at the time of surveillance colonoscopy were compared between patients with and without NAFLD using propensity score matching analysis. In an analysis of matched cohort of 441 patients, the cumulative rates of overall CRN occurrence at 3 and 5 years after index colonoscopy were higher in subjects with NAFLD than in those without NAFLD (9.1% vs. 5.0% & 35.2% vs. 25.3%, P = 0.01). Cox regression analysis showed that NAFLD independently increased the risk of overall CRN occurrence with marginal significance (adjusted hazard ratio [aHR]: 1.31 95% CI: 1.01-1.71, P = 0.05). Additionally, NAFLD was associated with the development of 3 or more adenomas at the time of surveillance colonoscopy (aHR: 2.49, 95% CI: 1.20-5.20, P = 0.02). In subgroup analysis based on index colonoscopy risk categories, the effect of NAFLD on the overall CRN occurrence at the time of surveillance colonoscopy was confined to the normal group (aHR: 1.47, 95% CI: 1.05-2.06, P = 0.02). Regarding advanced CRN occurrences at the time of surveillance colonoscopy, age was the only significant risk factor (aHR: 1.06, 95% CI: 1.02-1.10, P = 0.001). NAFLD was associated with overall CRN occurrence, especially in patients with no adenoma at the index colonoscopy. NAFLD may be considered for the determination of the time-interval for surveillance colonoscopy, especially the patients with negative index colonoscopy findings.